Stress dan Perilaku Coping pada Caleg yang Gagal Menjadi Anggota DPRD pada Pemilu 2024 - Marfita Hikmatul Aini (JURNAL ILMIAH PENELITIAN MAHASISWA, 2024)
This research aims to investigate the level of stress and coping behavior in legislative candidates (candidates) who fail to become members of the Regional People's Representative Council (DPRD) in the 2024 General Election (Pemilu). The research method used is qualitative research with a phenomenological approach. Data was collected through in-depth interviews with 20 respondents who were legislative candidates who failed to be elected. Data analysis was carried out using a qualitative approach involving coding and thematic processes. The research results show that legislative candidates who fail to become members of the DPRD in the 2024 elections experience high levels of stress, especially after finding out the election results. Factors that cause stress include unmet expectations, pressure from political parties, and feelings of failure in achieving their political goals. In dealing with this stress, legislative candidates adopt various coping strategies, including denial, adjustment, and seeking social support. This research provides a better understanding of the psychological experiences of legislative candidates who fail to be elected, as well as the coping strategies they use. The practical implications of this research include providing psychological and social support for legislative candidates who experience failure in a political context Penelitian ini bertujuan untuk menginvestigasi tingkat stres dan perilaku coping pada calon legislatif (caleg) yang gagal menjadi anggota Dewan Perwakilan Rakyat Daerah (DPRD) pada Pemilihan Umum (Pemilu) 2024. Metode penelitian yang digunakan adalah penelitian kualitatif dengan pendekatan fenomenologi. Data dikumpulkan melalui wawancara mendalam dengan 20 responden yang merupakan caleg yang gagal terpilih. Analisis data dilakukan dengan menggunakan pendekatan kualitatif yang melibatkan proses pengkodean dan tematik. Hasil penelitian menunjukkan bahwa caleg yang gagal menjadi anggota DPRD pada Pemilu 2024 mengalami tingkat stres yang tinggi, terutama setelah mengetahui hasil pemilihan. Faktor-faktor yang menyebabkan stres antara lain ekspektasi yang tidak terpenuhi, tekanan dari partai politik, dan perasaan gagal dalam mencapai tujuan politik mereka. Dalam menghadapi stres tersebut, caleg mengadopsi berbagai strategi coping, termasuk penolakan, penyesuaian diri, dan pencarian dukungan sosial. Penelitian ini memberikan pemahaman yang lebih baik tentang pengalaman psikologis caleg yang gagal terpilih, serta strategi coping yang mereka gunakan. Implikasi praktis dari penelitian ini termasuk penyediaan dukungan psikologis dan sosial bagi caleg yang mengalami kegagalan dalam konteks politik.